Empowering Minority Voices: Female Leadership Dynamics in Islamic Philanthropy Institution and Religious Outreach Movement - Nugroho, Diyas; Alves, Raul Manuel Costa (Potret Pemikiran, 2024)
Women's leadership in Islamic philanthropic institutions continues to face various structural and cultural challenges, despite having great potential for social transformation. These challenges include limited representation in leadership positions, cultural barriers, and complexities in aligning traditional and modern management approaches. This study analyzes the dynamics of women's leadership in Islamic philanthropic institutions, focusing on role transformation, adaptation strategies, and the impact of dual roles as institutional leaders and socio-religious activists. This qualitative research employs a single case study design at BAZNAS Sleman Regency, using in-depth interviews, participatory observation, and document analysis during July 2024. Data were analyzed using a thematic analysis approach with method triangulation to ensure findings' credibility. Women's leadership demonstrated effectiveness in improving institutional performance, evidenced by a 16.7% increase in zakat collection from 9.6 Billion to 11.2 Billion within a year. The integrative leadership model combining institutional roles and socio-religious activism proved effective in the context of Islamic philanthropy. The success of women's leadership in Islamic philanthropy depends on the ability to integrate traditional values with modern management and develop adaptation strategies suitable to local socio-cultural contexts.